Uji Efektivitas Kulit Buah Jengkol (Pithecolobium lobatum) Terhadap Kematian Siput Murbei (Pomacea canaliculata) - Puji Astuti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2013)
The purpose of this study is to obtain solutions in the potential development of botanical pesticides, cheaper, easier to come by, do not damage the environment and are not toxic. In addition, to determine the effect of the most effective ways against death of Siput Murbei  (P. canaliculata). Research carried out for two months, in the area Lempake Village, District of North Samarinda, Samarinda. The research used Completely Randomized Design (CRD) consisting of four treatments were repeated four (4) times, namely: Without giving jengkol skin or controls (a0), chopped jengkol skin 1 kg plot-1 or 2500 kg ha-1 (a1) , mashed jengkol skin 1 kg plot-1 or 2500 kg ha-1 (a2), soaked jengkol skin 1 kg plot-1 or 2500 kg ha-1 (a3). Results of the research indicated that: (1). Jengkol (Phitecolobium lobatum) fruit skin can be used as a plant-based pesticides to kill pests Siput Murbei (Pomaceaecanaliculata). (2). Without     jengkol friut skin (a0) no one died and suffered breeding, whereas rind jengkol given on day 15 died. (3). jengkol friut skin giving way most effective is soaked, because of the rapid death rate, ie 8.36 days, 8.67 days chopped, pounded and 9.17 days. Thus jengkol fruit skin effective in killing Siput Murbei.